Landing Success Rate During the Artistic Gymnastics Competition of the 2000 Olympic Games: Implications for Improved Gymnast/Mat Interaction - McNitt-Gray, J.; Requejo, P.; Costa, K.; Mathiyakom, W. (coachesinfo.com, 2002)
The low success rate associated with landings performed during Olympic competition emphasizes the difficulty of competition style landings. The between task differences in performance errors (ratio of under rotated vs. over rotated landings) suggests momentum control strategies implemented in preparation for contact must accommodate for between task differences in momentum conditions at touch down. Momentum conditions at the time of apparatus departure may also play a role in landing success in that flight time, angular momentum, and horizontal momentum of the total body center of mass is defined at the time of apparatus departure. Between Olympic comparisons of landing success rates may be misleading in that the F.I.G. Code of Points is a working document that evolves with the sport. For example, the skills performed during previous Olympic Games are likely to have imposed different momentum conditions from those performed during the 2000 Olympic Games. For example, lines have been placed in the landing area of the men's vaulting event to encourage a minimum horizontal displacement during the flight phase. These technical constraints imposed on gymnastics skills modify the mechanical objective of the task and subsequently the momentum conditions at landing. Successful performance is dependent on the ability of the gymnast to utilize features of the apparatus and landing surface. To facilitate performance and effective load distribution within the musculoskeletal system, the landing surfaces used by gymnasts during competition need to be predictable and complement the physiological capabilities of the gymnast to control momentum and absorb energy load during landing. Standardization of apparatus used during competition by the Apparatus Commission and advance communication of the specific apparatus to be used in competition provide the gymnasts with critical information that will enable them to better prepare for competition conditions. Prior to competition, however, gymnasts have limited exposure to the actual landing surfaces and apparatus used during the competition (e.g. equipment mounted on competition podium in the venue). The FIG has taken steps towards improving the interaction between the gymnast and the apparatus by improving communication between equipment manufacturers, coaches, medical personnel and scientists through publications, conferences, and commissions.